How an Automotive Brand Corrupts: Insights from the 2015's Volkswagen Dieselgate - Fanani, Roby Zul; Sartika, Forestya; Bioldy, Ersal; Novianda, Olga; Lasuardy, Andi; Permatasari, Yulinda S.; Murtadha, Hasan Ali (Jobmark: Journal of Branding and Marketing Communication, 2020)
The giant German automotive manufacturer, Volkswagen (VW), was involved in the most significant case of falsifying emissions standards in automotive history in 2015, and this case caused VW to suffer losses of €32 billion. VW is suspected of manipulating verbal and non-verbal messages by involving many media. This article aims to dissect the communication corruption committed by VW in falsifying its standard emission test data. Communication corruption is an act or event in the communication process that reduces the rights of the public or audience to receive messages completely and correctly according to the facts, both normative facts and contemplative facts, by taking advantage of the power, strength, or authority they possess. In analyzing this theory, four dimensions can be seen: message, media, context, and behavior. The analysis results show that VW corrupted the exhaust emissions message on diesel-engined vehicles. VW admitted its mistake after compelling evidence and mounting public pressure. In the media dimension, VW corruptively communicates its benefits through television commercials, outdoor advertising, and digital media. The corrupt communication context of VW includes culture, situation, targets, norms, and values. At the same time, the behavioral dimension is related to immoral and even illegal actions from the Dieselgate scandal, such as manipulating special software on diesel engines to cheat emissions tests to smooth distribution permits. This case teaches brands that messages should always be conveyed openly and transparently so as not to harm many parties, especially the company itself.